Facile synthesis of Fe3+ doped La2CuO4/LaFeO3 perovskite nanocomposites: Structural, optical, magnetic and catalytic properties. (September 2019) - Sukumar, M.; Kennedy, L. John; Vijaya, J. Judith; Al-Najar, B.; Bououdina, M.
Abstract: La2 CuO4 /LaFeO3 perovskite nanocomposites were prepared using a microwave combustion technique. The structural characterization by XRD and Rietveld refinements confirmed that Fe 3+ substitution in La2 CuO4 (LFC) induced the crystallization of secondary LaFeO3 phase. The orthorhombic/cubic nanostructured composites exhibited an average crystallite size in the range 37–47 nm and 14–39 nm, respectively. FTIR spectra revealed bands at 517, 683, and 561 cm −1, characteristics of perovskites orthorhombic and cubic stretching modes. With the increase in Fe 3+ doping concentration, the optical band gap increased gradually. Surface morphology showed nanosized crystalline grains agglomerated with spherical and non-spherical shapes. The doping dependence of the magnetisation indicated magnetic transition from ferromagnetic to the paramagnetic state at room temperature. The bifunctional nanocomposites La2 CuO4 /LaFeO3 exhibited excellent catalytic performance and better conversion efficiency (conversion 100% and selectivity 98.6%) for glycerol.